Congress and the politics of sports - Campbell, Colton C., 1965-; Dulio, David A. (New York, NY : Routledge, 2024)
"This volume covers an aspect of Congress mostly untouched in literature, examining Congress through the lens of sports. Across a set of broad and probing chapters, this book offer insights into some of the historic and contemporary challenges that sports have presented to Congress, along with highlighting the ways in which Congress has impacted the sports industry. The authors utilize a wide range of case studies to provide readers with a contemporary view of the inter-play between Congress and sports, at both amateur and professional levels. Perspectives are drawn from an interdisciplinary and cross organizational roster of authors, uniquely positioned to discuss various their subjects. With real attention now being given to issues associated with sports, and an increasing number of lawmakers using sports to push policy agendas and create legislative opportunities, this book will be a vital resource for understanding the dynamic relationship between the two entities. Grounded in relevant literature, and written in an accessible and engaging manner, Congress and the Politics of Sports will be of great interest to both academic researchers and practitioners involved with US politics, Congress and congressional studies, public policy, sports studies and sport history"--
The role and influence of sports on Capitol Hill / David A. Dulio, Colton C. Campbell -- 'A picture of community' : the origins and longevity of the Congressional Baseball Game / Mathew A. Wasniewski -- Winning by associaon : how Congress uses sports commemoraves / Jacob R. Straus, Jared C. Nagel -- Congress and the baseball steroids scandal : Congress steps up, baseball strikes out / Greg McCarthy -- Professional team sports and Congress : invesgaons, antrust, mergers and media / David George Surdam -- Congress, teams, and power dynamics in sing sports facilies / Eric Heberlig, David Swindell -- Title IV, gender equity, and college sports / Ellen J. Staurowsky -- Congress's growing role in college sports / Brian Porto.
Keywords: United States. -- Congress; Sports -- Political aspects -- United States; Sports and state -- United States; SPORTS & RECREATION / General; POLITICAL SCIENCE / Government / Legislative Branch